Magnetic resonance imaging histogram analysis of amygdala in functional neurological disorder Histogram Analysis of Amygdala in Functional Neurological Disorder - Baykara, Murat; Baykara, Sema; Atmaca, Murad (Elsevier Ireland Ltd, 2022)
[Abstract Not Available]
Keywords: Childhood Abuse; Emotion